Data for "An application of upscaled optimal foraging theory using hidden Markov modelling: year-round behavioural variation in a large arctic herbivore" - Schmidt, Niels Martin (Zenodo, 2020)
Data for the article “An application of upscaled optimal foraging theory using hidden Markov modelling: year-round behavioural variation in a large arctic herbivore” By LT Beumer, J Pohle, NMS Schmidt, M Chimienti, JP Desforges, LH Hansen, R Langrock, SH Pedersen, M Stelvig, FM van Beest The data set includes three files: Areadme file describing the data files and two data files accompanying the above publication. Combined, thetwo data files represent the dataset collected by GPS collars fitted on 19 female muskoxen in northeast Greenland (28 muskox-years with 153-1062 observation days/animal) and associated extracted covariates, divided into a summer and winter season dataset as modelled in the article. Data here are given as included in the models (for a description of cleaning procedures, see article). All continuous, non-cyclical covariates were standardised to have zero mean and unit standard deviation to improve numerical stability of parameter estimation. This is indicated by “_scaled” in the column name. For further queries please contact nms@bios.au.dk